A Comparative Study of Local and City Governance Systems in Pakistan and China - Jabeen, Musarrat (Journal of Pakistan Administration, 2022)
This research paper attempts to analyze local self-government institutions and processes established in China and Pakistan. An overall assessment of the established systems in both nation-states shows the relative success of China. Firstly, historical developments before the establishment of both countries caused a systematic difference in the development of local governments, which made it relatively easier for China to establish grassroots systems across the country. For Pakistan, the colonial legacy continues to this day, due to which the country has been unable to make meaningful strides in the sector of local governance. Secondly, China is a socialist state and consists of a hierarchical structure where every level is responsible to the next higher level. Although the local government system is efficient and effective in service delivery, it lacks participatory democracy. Conversely, Pakistan is a federal state with parliamentary democracy. Due to politico-bureaucratic nexus, broad-based representative local governments could not be established. Thirdly, China’s success attributes to a centralized system and goal alignment between various tiers of the government in the country. In Pakistan, however, there are multiple stakeholders with vested interests in the country that go beyond economic development. Pakistan’s politics has been marred by a power struggle between democratic political forces and the military establishment. Fourthly, the CCP maintains a favourable opinion among the masses in China. All measures that advance that image are taken by the central authorities, even at the expense of local governments. In Pakistan’s case, the attitude towards elected and provincial governments is hostile. Setting up an autonomous elected local government system can posit significant dangers to the vested interests of powers at the upper echelons of the political governments. Lastly, the 18th Amendment has provided provinces complete control in establishing local governments in their areas. Learning from China, Pakistan needs a robust local government system that suits its context, is financially viable, transparent, devoid of bureaucratic, political rifts, and efficient service delivery mechanisms. However, one should be aware that China and Pakistan’s governance structures are poles apart, and one can only draw lessons from China’s local government system.